Pharmacokinetics and Safety of Single Intravenous Doses of Ceftolozane/Tazobactam in Children With Proven or Suspected Gram-Negative Infection. Issue 11 (November 2018) - Bradley, John S.; Ang, Jocelyn Y.; Arrieta, Antonio C.; Larson, Kajal B.; Rizk, Matthew L.; Caro, Luzelena; Yang, Shan; Yu, Brian; Johnson, Matthew G.; Rhee, Elizabeth G.
Abstract : Background: Drug-resistant Gram-negative bacteria are a growing threat to children; thus new antibiotics are needed to treat infections caused by these pathogens. Ceftolozane/tazobactam is active against many Gram-negative pathogens and is approved for treatment of complicated intra-abdominal and urinary tract infections in adults, but has not been evaluated in children. Methods: This phase 1, noncomparative, open-label, multicenter study characterized the pharmacokinetics (by noncompartmental analysis), safety, and tolerability of single intravenous doses of ceftolozane/tazobactam in pediatric patients (birth [7 days postnatal] to < 18 years of age) with proven/suspected Gram-negative infection or receiving perioperative prophylaxis (clinicaltrials.gov NCT02266706). Patients were enrolled into 1 of 6 age groups to receive a single, age-based ceftolozane/tazobactam dose, with timed blood sample collection for determining plasma concentrations of ceftolozane and tazobactam. Safety and tolerability were also evaluated. Results: Thirty-seven patients received study drug; 34 were included in the pharmacokinetic population. Ceftolozane and tazobactam pharmacokinetic parameters were generally comparable for patients 3 months to < 18 years of age. Patients from birth (7 days postnatal) to < 3 months of age had lower clearance than older children, likely due to the immature renal function of these young infants. No deaths, study drug-related serious adverse events, or clinically significant laboratory abnormalities were observed after administration of ceftolozane/tazobactam. Conclusions: The doses evaluated in this study yielded ceftolozane/tazobactam exposure levels generally comparable with those in adults. Single doses of ceftolozane/tazobactam were well-tolerated, and no safety concerns were identified. These data informed pharmacokinetic/pharmacodynamic models to derive pediatric dose recommendations for phase 2 ceftolozane/tazobactam clinical trials. Abstract : Supplemental Digital Content is available in the text.